Networks for resilience: The role of social capital - Bernier, Quinn; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2014)
This report investigates the under-explored role that local forms of social capital, in particular local organizations and social networks, play in enhancing resilience. The case studies used are of Ethiopian funeral societies and Filipino migrant networks. MAIN FINDINGS Local social capital systems can play a positive role in individual, household, and community risk-smoothing and risk-sharing practices by providing bonding, bridging, and linking capital that allow people to better cope, adapt, and transform. Impact is context specific, however, and can vary in the strength and the social group or groups covered. Community groups are also generally much more effective in dealing with shocks that affect individual members rather than many in the group, but face challenges when mobilizing resources that are outside of communities.